Consumption of a Single Dose of Prebiotic Galacto-Oligosaccharides Does Not Enhance Iron Absorption from Micronutrient Powders in Kenyan Infants: A Stable Iron Isotope Study. Issue 5 (9th March 2021) - Mikulic, Nadja; Uyoga, Mary A; Paganini, Daniela; Mwasi, Edith; Stoffel, Nicole U; Zeder, Christophe; Karanja, Simon; Zimmermann, Michael B
ABSTRACT: Background: Long-term feeding of prebiotic galacto-oligosaccharides (GOS) increases iron absorption in African infants, but the underlying mechanism and how long GOS need to be fed to infants to achieve an increase in absorption is uncertain. Objectives: In Kenyan infants, we tested whether the addition of GOS to a single test meal would affect iron absorption from a micronutrient powder (MNP) containing ferrous sulfate (FeSO4 ) and another MNP containing ferrous fumarate (FeFum) and sodium iron ethylenediaminetetraacetate (NaFeEDTA). Methods: In a randomized-entry, prospective crossover study, iron deficient (87%) and anemic (70%) Kenyan infants ( n   = 23; mean ± SD age, 9.9 ± 2.1 months) consumed 4 stable iron isotope–labeled maize porridge meals fortified with MNPs containing 5 mg iron as FeFum + NaFeEDTA, or FeSO4, either without or with 7.5 g GOS. The primary outcome, fractional iron absorption (FIA), was assessed by erythrocyte incorporation of isotopic labels. Data were analyzed using a 2-way repeated-measures ANOVA. Results: There was no significant interaction between GOS and the iron compounds on FIA, and the addition of GOS did not have a significant effect on FIA. There was a statistically significant difference in FIA between the meals fortified with FeSO4 and with FeFum + NaFeEDTA ( P   < 0.001).Given with GOS, FIA from FeSO4 was 40% higher than from FeFum + NaFeEDTA ( P   < 0.001); given without GOS, it was 51% higher ( P   < 0.01). Conclusions: The addition of GOS to a single iron-fortified maize porridge test meal in Kenyan infants did not significantly increase iron absorption, suggesting long-term feeding of GOS may be needed to enhance iron absorption at this age. This study was registered at clinicaltrials.gov as NCT02666417.